“I Did Not Consent To” - Dewey, Fred (HannahArendt.net, 2022)
“I Did Not Consent To” is excerpted from Prairie Fires, a book Fred had been working on since 2016 and left on his computer when he died June 2, 2021. In the process of reading Prairie Fires, the editors were struck by how many times Fred used the word “consent” in a certain 12-page passage (ninety-seven times) until this word picked up steam in a kind of incantatory rhythmic procession as if it were creating its own logic, a logic of both screed and poetry. The reader will notice Fred’s adopting James Baldwin’s tactic of “accepting responsibility” for events Fred never consented to, thus proposing that our complicity licenses us agency to change the system. The book length Prairie Fires will be issued by IFSF Publishing in 2023.